Penanaman Sikap Kepemimpinan dalam Gerakan Pramuka - Ahmad Gupron; Lukman Lukman; Victoria Karjiyati (Universitas Bengkulu, 2019)
The purpose of this study is to describe the planting of leadership attitudes in the Scout Movement. This research is a descriptive study with a type of qualitative research. Data collection techniques using observation, interviews, and documentation. Test data credibility through increased perseverance, triangulation and member checking. Analysis of the data that has been obtained through data reduction, data presentation, and drawing conclusions. The results of this study are in instilling leadership attitudes in accordance with the Articles of Association (AD) of the Scout Movement applying the principles of leadership; increase caring) Scoutmaster coaches always care about what students will do, always provide motivation and support to students so students can increase their confidence, care, enthusiasm and other positive things. The conclusion obtained is that the planting of leadership attitudes can be done through the Scouting movement. In the Scout Movement to instill leadership attitudes applying the Scouting Method, including; Practicing the Scout Code of Honor (satya and darma), Learning While Doing, Team Systems, Outdoor Activities, and Partnerships With Adults.